Breaching the wall. (November 2018) - Economou, Anastassios
Protein translocation across bacterial membranes can take many routes through dedicated transport machines. A new study finds thatSalmonella Typhi utilizes a distinct pathway to translocate typhoid toxin across the peptidoglycan layer and prime the bacterium for host intoxication.